(untitled) (Annals of Medical Research, 2021)
Aim: This study was conducted for the purpose of identifying the relation between the attitudes of nursing undergraduate students on gender equality and dating violence. Material and Methods: The study was conducted with 310 undergraduate students who studied in the nursing department of a university. The Personal Information Form, Gender Equality Scale (GES) and Dating Violence Scale (DVS) were used as the data collection tools. Shapiro-Wilk test, histogram, Q-Q graphics, Mann-Whitney U, Kruskal-Wallis and Spearman’s correlation test were used in data analysis. Before beginning the research, ethical approval was obtained from the Ethical Committee. Results: Regarding dating relations of nursing students; 39.4% stated about their dating relationships that they had a dating relationship, 78.0% stated that they continued their relationship “orderly/serious”, 7.3% stated that they “committed violence” in their dating relationship, and 2.4% stated that they “were exposed to violence” in their dating relationship. It was identified that the students had the lowest score from the emotional and economical sub-scale and that the students did not generally support the dating violence. A positive and moderate relation was determined between the GES and the DVS scores of the nursing students (p0.05). Conclusion: In nursing education curricula, it is necessary to address the concept of gender together with the dating violence.